Impact of Alcoholism on the Family Life of Low-Income Adults in Rural Communities in Brazil (CIPEEX, 2025)
This study aimed to analyze the impact of alcoholism on the family dynamics of low-income adults living in rural Brazilian communities. The research was developed through a narrative literature review with a qualitative approach, gathering and discussing scientific productions published between 2014 and 2024 in databases such as SciELO, MEDLINE, LILACS, BVS, among other academic sources. The results showed that the abusive consumption of alcohol significantly compromises family cohesion, generating marital conflicts, weakening affective bonds, emotional overload, and psychological distress, especially among spouses and children. The findings also pointed to the association of alcoholism with common mental disorders, such as anxiety, depression, and chronic stress, which are exacerbated by socioeconomic vulnerability and limited access to health services in rural areas. Furthermore, it was identified that cultural factors and the normalization of alcohol consumption in community contexts hinder the search for treatment and the implementation of effective coping strategies. The study concluded that alcoholism, as a biopsychosocial phenomenon, requires integrated responses involving public health policies, social support, and psychosocial interventions adapted to rural specificities, in order to reduce the damages caused by abusive consumption and to strengthen family support networks.
Keywords: alcoholism; family; rural communities; mental health; social vulnerability